The Effectiveness of Pregnancy Exercise In Relieving Back Pain During Third Trimester of Pregnancy At BPM Nurhidayah Cisarua Bogor In 2021 - Nengsih, Dwi Purnama; Syamsiah, Siti; Suciawati, Anni (STRADA : Jurnal Ilmiah Kesehatan, 2021)
One way to improve health during pregnancy is to do light exercise such as pregnancy exercise. This study aimed at finding out the effectiveness of pregnancy exercise in relieving back pain in third trimester pregnant women. Method: This study used quasi-experimental research design with one-group pretest-posttest approach. A sample of 20 was obtained using purposive sampling technique. Data were analyzed using Paired T-test. Results of difference test using paired sample t-test obtained mean difference of 3.80 with significance value of 0.002 < 0.05, indicating that pregnancy exercise has been proven to be effective in relieving pain in third trimester pregnant women. Results of mean difference test, t-test and correlation test have proven that pregnancy exercise is effective in relieving back pain in third trimester pregnant women at BPM Nurhidaya Cisarua Bogor in 2021